2004
DOI: 10.1177/153537020422900304
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous Running Increases Growth Hormone and Insulin-Like Growth Factor-I Without Altering Ghrelin

Abstract: It has been suggested that ghrelin may play a role in growth hormone (GH) responses to exercise. The present study was designed to determine whether ghrelin, GH, insulin-like growth factor-I (IGF-I), and IGF-binding protein-3 (IGFBP-3) were altered by a progressively intense running protocol. Six well-trained male volunteers completed a progressively intense intermittent exercise trial on a treadmill that included four exercise intensities: 60%, 75%, 90%, and 100% of Vo2max. Blood samples were collected before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
91
1
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 40 publications
(54 reference statements)
7
91
1
5
Order By: Relevance
“…The results of the Broglio et al (2001) study suggest that ghrelin could directly stimulate glycogenolysis, which takes part also in exercise conditions. Surprisingly, the exercise had decreased effect or no effect on plasma ghrelin in adult humans (Kraemer et al, 2004;Ghanbari-Niaki, 2006;Vestergaard et al, 2007). In the present study, a similar effect can be observed in 2-year old and older trotters.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the Broglio et al (2001) study suggest that ghrelin could directly stimulate glycogenolysis, which takes part also in exercise conditions. Surprisingly, the exercise had decreased effect or no effect on plasma ghrelin in adult humans (Kraemer et al, 2004;Ghanbari-Niaki, 2006;Vestergaard et al, 2007). In the present study, a similar effect can be observed in 2-year old and older trotters.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, exercise has been reported not to influence plasma ghrelin levels even at high exercise intensities [28][29][30]. We are unaware of other published data in which the plasma ghrelin response to exercise has been studied in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have focused on aerobic (cardiovascular) exercise (31), with only three studies examining the effects of resistance (muscle strengthening) exercise, and these have reported contradictory effects (21,33,47). Resistance exercise is a key component of exercise recommendations for weight control (2) and public health (23, 42); thus, it is important to clarify the effects of resistance exercise on hunger and gut hormones.The effect of acute exercise bouts on total plasma ghrelin concentrations is controversial, with studies reporting no changes either during or postexercise (10,15,26,27,32,39,43,45,47), as well as increases (14,17,25,44) and decreases (21,33,48,50). Acylation of ghrelin is thought to be essential for appetite regulation because only the acylated form of the hormone can cross the blood-brain barrier (41).…”
mentioning
confidence: 99%
“…The effect of acute exercise bouts on total plasma ghrelin concentrations is controversial, with studies reporting no changes either during or postexercise (10,15,26,27,32,39,43,45,47), as well as increases (14,17,25,44) and decreases (21,33,48,50). Acylation of ghrelin is thought to be essential for appetite regulation because only the acylated form of the hormone can cross the blood-brain barrier (41).…”
mentioning
confidence: 99%